Inflammatory Markers and Frailty in Long‐Term Care Residents. Issue 8 (21st March 2017) - Langmann, Gabrielle A.; Perera, Subashan; Ferchak, Mary A.; Nace, David A.; Resnick, Neil M.; Greenspan, Susan L.
Abstract : Objectives: To determine whether proinflammatory biomarkers are associated with frailty assessed according to functional status, mobility, mental health, and falls over 24 months. Design: Secondary analysis of a 2‐year double‐blind clinical trial for osteoporosis. Setting: Nursing homes and assisted living facilities. Participants: Women aged 65 and older with osteoporosis in long‐term care (LTC) (N = 178). Measurements: Baseline serum concentrations of proinflammatory cytokines and soluble receptors (high sensitivity C‐reactive protein (hs‐CRP), tumor necrosis factor alpha (TNF α ) and its two receptors (TNF α ‐R1 and TNF α ‐R2), interleukin‐6 (IL‐6), soluble IL‐6 receptor (sIL‐6R), IL‐10), functional status assessed according to activities of daily living, the Nursing Home Physical Performance Test, gait speed, cognitive status, mental health, and falls. Results: At baseline, older age was moderately associated with higher serum concentrations of hs‐CRP (correlation coefficient ( r ) = 0.22), TNF α ‐R1 ( r = 0.36), TNF α ‐R2 ( r = 0.34), and IL‐10 ( r = 0.16) (all P < .05). Frail participants had significantly higher hs‐CRP, TNF α ‐R1, TNF α ‐R2, IL‐6, and IL‐6‐sR levels (all P < .05) than those nonfrail participants. Higher baseline hs‐CRP and IL‐6 levels were associated with worse physical performance and gait speed at 12 months independent of age, zoledronic acid use, and comorbidity (| r | = 0.25–0.30; all P < .05). Inflammatory markers were not significantly associated with incident falls. Conclusions: Higher proinflammatory biomarker levels are associated with frailty and poorer function and mobility in older women residing in LTC facilities.